Analysis of the Habitat Fragmentation of Ecosystems in Belize Using Landscape Metrics - Flowers, Bryon; Huang, Kuo-Tsang; Aldana, Gerardo O. (Sustainability, 2020)
Landscape metrics have been of game changing importance in the analysis of ecosystems’ composition and landscape cohesion. With the increasing urban and agricultural expansion, the natural flora and fauna of many highly diverse areas have been degraded. Fragmentation of ecosystems and habitats have stressed the biodiversity of Belize. To understand the dynamics of this change, a study was conducted using three moderately separate years of ecosystem landscape data. The metrics used for the analysis were area-weighted mean shape index (AWMSI), mean shape index (MSI), edge density (ED), mean patch size (MPS), number of patches (NUMP), and class area (CA). These metrics were produced for the years 2001, 2011, and 2017. The classes of agricultural use, lowland savannas, mangroves and littoral forests, urban, and wetlands were the subjects for analysis. Using the GIS extension Patch Analyst, parametric runs were performed. From these results, a one-way ANOVA test of the NUMP, Tukey HSD test, and Scheffé Multiple Comparison test were performed. The results indicate that there has been significant habitat fragmentation, especially from the years 2001 to 2011. Agricultural areas increased by 19.37% in just 10 years, with the NUMP of some habitats increasing by 284%. The results also show fluctuation in ED and a decrease in overall MPS, all indicating high fragmentation. These changes have been mostly induced due to the expansion of agricultural activities and urbanization, especially in the northern parts of Belize. It is imperative that additional policies be implemented to deter the effects of habitat fragmentation upon the existing ecosystems of Belize and elsewhere.